Implementation of Violation of E-Tilang Regulations in the Analysis of Human Resources and Criminal Law Perspectives in Indonesia - Nining Yurista Prawitasari; Apri Aji Setyawan (Budapest International Research and Critics University, 2023)
The fine process that has been carried out conventionally is expected to be able to reduce the level of traffic violations, whereas the conventional ticket system still uses a paper system in one of its implementations. A manual ticket system that uses blanks or ticket letters. When a traffic user is proven to have committed a mistake or violation, the police officer will take several actions in accordance with applicable regulations. At present, the National Police have innovated by carrying out e-tickets by monitoring ETLE cameras. The theory used is the theory of human resources and the theory of bureaucratic reform and law enforcement theory. The methodology used is a qualitative approach. In research, the results of this research are in the form of an understanding that e-tickets have caused many violations, whether this is due to human resources or in the application of a policy whether there is a lack of optimization in conducting socialization.